2019
DOI: 10.1007/s11101-019-09627-x
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals in cancer prevention: modulating epigenetic alterations of DNA methylation

Abstract: Cancer can take many years to develop from initiation to progression. The long period of development might represent an opportunity to use multi-functional, multi-targeted preventive drugs to block or reverse tumorigenesis. One path to cancer prevention could be to target and reverse the early epigenetic alterations. Unlike genetic mutations, they are potentially reversible and can be restored to their normal state. Epidemiological studies have revealed the close link between rich diets in bioactive compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 111 publications
(122 reference statements)
0
23
0
Order By: Relevance
“…Rapha Myr ® induces the upregulation of DNA methyltransferase1 (DNMT1) mRNA level and global DNA hypermethylation, unlike the results from other authors reporting that SFN induces DNA hypomethylation and decreased levels of DNMT1 in several types of cancer cells (breast, prostate, colon and liver) [ 55 ]. Among epigenetic markers, the sirtuins, a family of NAD + −dependent histone deacetylases comprising seven proteins from Sirt1 to Sirt7, are involved in many crucial cellular processes [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 88%
“…Rapha Myr ® induces the upregulation of DNA methyltransferase1 (DNMT1) mRNA level and global DNA hypermethylation, unlike the results from other authors reporting that SFN induces DNA hypomethylation and decreased levels of DNMT1 in several types of cancer cells (breast, prostate, colon and liver) [ 55 ]. Among epigenetic markers, the sirtuins, a family of NAD + −dependent histone deacetylases comprising seven proteins from Sirt1 to Sirt7, are involved in many crucial cellular processes [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 88%
“…As known, epigenetic modifications of chromatin are reversible and inherited, so they represent promising targets for the development of novel drugs targeting the epigenome which can contribute to amelioration of conventional therapies in cancer [44]. It has been reported that a diet rich in phytochemicals may act through epigenetic mechanisms such as modulation of DNMTs and HDACs activities that can significantly reduce the risk of cancer development by regulating the expression of oncogenes and tumor suppressor genes [45]. Cancer treatments are involved using chemo-radio therapeutic agents, kinase inhibitors, antibodies as well as certain compounds that stimulate the immune system, generally.…”
Section: Therapeutic Potential Of Polyphenols On Dna Methylationmentioning
confidence: 99%
“…Cancer treatments are involved using chemo-radio therapeutic agents, kinase inhibitors, antibodies as well as certain compounds that stimulate the immune system, generally. Meanwhile, demethylating drugs modified gene expressions by reversing the aberrant epigenetic alterations acquired during tumorigenesis [44,45]. In this context, polyphenolic flavonoid compounds may represent an alternative therapeutic option for cancer treatment.…”
Section: Therapeutic Potential Of Polyphenols On Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] Cancer pathologies are multistep processes resulting from the interplay of genetics and epigenetics alterations as well as from environmental and lifestyle factors. [ 3 ] Among the most widely used treatments to fight these pathologies, such as surgery, radiation, chemo‐ and hormonal treatments, chemotherapy is considered the most effective and extensively used method in most types of cancers. Nevertheless, the current therapeutic regimes are often limited by the systemic toxicity of anticancer drugs, mainly due to the lack of selectivity for cancer cells and tissues, the development of drug‐resistant cancer cells, and to the hydrophobic nature of many anticancer drugs which often leads to a poor cell distribution.…”
Section: Introductionmentioning
confidence: 99%